An overview and visual analysis of research on government regulation in healthcare - Qi, Min; Ren, Jianming (Frontiers in Public Health, 2023)
Objective During the period of COVID-19, government regulation (GR) played an important role in healthcare. This study examines the current research situation of GR in healthcare, discusses the research hotspots, the most productive authors and countries, and the most common journals, and analyzes the changes in GR in healthcare before and after the outbreak of COVID-19. Methods This study followed PRISMA guidelines to collect literature on GR in healthcare. And the VOSviewer software was used to perform a quantitative analysis of these documents to obtain a visual map, including year, country, institution, journal, author, and research topic. Results A total of 1,830 papers that involved 976 academic journals, 3,178 institutions, and 133 countries were identified from 1985 to 2023. The United States was the country with the highest production (n = 613), followed by the United Kingdom (n = 289). The institution with the largest number of publications was the University of London in the UK (n = 103); In the author collaboration network, the biggest cluster is Bomhoff M, Bouwman R, Friele R, et al. The top five journals in terms of the number of articles were BMC Health Services Research (n = 70), Plos One (n = 35), Health Policy (n = 33), Social Science & Medicine (n = 29), Health Policy and Planning (n = 29), and Frontiers in Public Health (n = 27). The existing literature mainly focused on “health policy,” “public health,” “China,” “mental health,” “India,” “qualitative research,” “legislation,” and “governance,” et al. Since 2020, research on “COVID-19” has also become a priority in the domain of healthcare. Conclusion This study reveals the overall performance of the literature on GR published in healthcare. Healthcare needs GR, especially in response to the COVID-19 epidemic, which has played an irreplaceable role. The outbreak of COVID-19 not only tested the health systems of various countries, but also changed GR in healthcare. With the end of COVID-19, whether these changes will end remains to be further studied.